Twórcy ukraińskiej geopolityki = The founders of the Ukrainian geopolitics - Eberhardt, Piotr (1935–2020) (IGiPZ PAN, 2009)
In the article, the introductory part presents the historical and political conditions behind the development of the Ukrainian national movement. A great influence on that movement’s first appearance was exerted by the Brotherhood of Cyril and Methodius, whose members were Mykola Kostomarov, Pantheleon Kulish and Taras Shevchenko. The political situation in the Austrian province of Galicia and within Ukrainian territories belonging to Russia is then presented, attention being paid to the essential differences exerting a more significant impact on the way views on the future of Ukraine developed. The programmes of the Ukrainian organisations then in existence are presented, along with the views of the leading activists seeking to defend the interests of the Ukrainian people. It is notable how the latter were limited to the formulation of postulates as regards language and culture. Beyond that, one of the first scholars to posit the need for a fully sovereign Ukrainian statehood was Mykola Mikhnovs’kiy, who wrote extensively of the so-called samostiyna Ukraina („self-standing Ukraine”). This is what assures Mikhnovs’kiy’s place back at the outset of the history of Ukrainian geopolitics. It was he who proclaimed the necessity of establishing a sovereign Ukrainian state situated „between the Carpathians and the Caucasus”. Once the work of that scholar has been outlined, the paper goes on to present the views of four consecutive activists and political writers, each dealing with the geopolitical situation of the Ukrainian territories. The developers of the foundations for the new scientific discipline of geopolitics, by taking advantage of the achievements of geography and political science, are seen to be: Stepan Rudnytskyi, Dmytro Dontsov, Volodymyr Kubiyovich’ and Yuriy Lypa. The relevant scientific vitae and achievements in the domain of geopolitics are provided in the paper. Rudnytskyi authored a book on the geography of Ukraine, in which he presented its geopolitical situation with respect to neighbours. At the same time, he formulated the concept of an alliance of countries situated between the Baltic and the Black Sea. Dontsov was in turn a proponent of social and national Darwinism, and was the intellectual father of the ideological direction called „integral Ukrainian nationalism”. His concepts were extremely nationalistic and he glorified the idea of the great Ukrainian state. Another scholar considered among the founders of Ukrainian geopolitics is Kubiyovich’, an outstanding geographer among the promoters of the idea that all the ethnically Ukrainian lands should be incorporated within one nation state (in the so-called sborna Ukraina or united Ukraine). In contrast, Lypa was the author of a consistent doctrine pointing to Ukraine’s status as a Black Sea country. This set him apart from the other Ukrainian geographers and politicians, who saw the future of Ukraine as lying in association with either the East or with the West. Having completed his presentation of and comments on the work of the aforesaid five Ukrainian scholars, the author concludes by suggesting that their scholarly achievements are an original and interesting, as well as creative, contribution to the domain of geopolitics as broadly conceived.
24 cm
Keywords: Ukraine; geopolitics; Ukrainian geopoliticians